O caminho das pedras : conhecendo melhor os usuários de crack do município do Recife-PE - Almeida, Renata Barreto Fernandes de (2011)
This research had as its main aim to portrait crack-cocaine users experience in the city of Recife. Subjects were crack-cocaine users, males and females, from 18 years old, undertaking treatment at drug addiction health services in Recife ( CAPSad and Instituto RAID ) during data collection. One subject from each CAPSad (06 in a whole) was interviewed and 06 subjects from Instituto RAID were interviewed. All designated by the health professional teams and with organized thoughts to describe their crack-cocaine use experiences, as well as with willingness to respond to a semi-structured interview. The research was qualitative with phenomenological background inspired by Husserl s theory and Giorgi s method. Basically, this method includes these steps: 1) reading the entire description of one subject in order to get a sense of the whole; 2) reading through the data a second time and marking those places in the description where a transition in meaning occurred from a psychological perspective (the meanings between transitions are called meaning units ); 3) reading all of the meaning units and interrogating them from what they reveal about the phenomenon of interest, in this case, the crack-cocaine use experience, in order to grasp the relevance of the subject s own words for the phenomenon of using crack-cocaine in as direct a manner as possible (this step is called the transformation of the subject s lived experience into direct psychological expression); 4) presenting a situated or general structure of the experience (synthesis of each report expressed as structure of experience); and, 5) comprehending the general synthesis which represents the essence of the phenomenon to all subjects investigated. The identification of crack-cocaine users experience in meaning units pointed out to several themes such as: the experience of being a crack-cocaine user; what took them to use this drug; the meaning of crack-cocaine in their lives; crack-cocaine use sensations; crack-cocaine death pleasure; compulsion guiltiness; losses related to the drug; family as an important factor to seek treatment; crack-cocaine and violence; treatment challenges; crack-cocaine use stigma; and, loss of control experienced by users. These complex issues expressed by research subjects set great challenges to health professional teams treating crack-cocaine users and draw attention to the need of permanent reflection of their practices